2017
DOI: 10.1590/0034-7167-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual well-being and quality of life of older adults in hemodialysis

Abstract: Objective: To analyze the relationship between spiritual well-being, sociodemographic, economic, religious, and health variables and the quality of life of older adults undergoing hemodialysis. Method: This was a cross-sectional and correlational study conducted with 169 older adults undergoing hemodialysis. The researchers conducted interviews to collect sociodemographic, economic, religious, and health data and applied the Spiritual Well-Being Scale (SWBS) and the WHO quality of life assessment (WHOQOL-BREF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 25 publications
5
45
0
18
Order By: Relevance
“…The results found that spiritual well-being is a significant predictor of HRQoL. This confirms the findings of previous studies (Nelson et al, 2009;Jahani et al, 2013;Park et al, 2014;Pilger et al, 2017). However, the mediation analysis showed that illness perception partially mediated spiritual well-being and HRQoL.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results found that spiritual well-being is a significant predictor of HRQoL. This confirms the findings of previous studies (Nelson et al, 2009;Jahani et al, 2013;Park et al, 2014;Pilger et al, 2017). However, the mediation analysis showed that illness perception partially mediated spiritual well-being and HRQoL.…”
Section: Discussionsupporting
confidence: 89%
“…Spiritual wellbeing can help patients overcome their anxiety and depression (Mills et al, 2015;Park et al, 2016) and significantly affects HRQoL. Some studies have found a significant relation between spiritual well-being and HRQoL (Jahani et al, 2013;Park, Lim, Newlon, Suresh, & Bliss, 2014;Pilger, Santos, Lentsck, Marques, & Kusumota, 2017). Improving patients' spiritual well-being would make them feel they are emotionally supported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, aging leads to a continuous and progressive decrease in the body's ability to maintain its homeostatic balance. Thus, older adults commonly face gradual decreases in their functional capacity, which may limit them in performing the activities of daily living (7) .…”
Section: Discussionmentioning
confidence: 99%
“…The search for the transcendent was related to spirituality that provided a search for meaning and answers to fundamental aspects of life. The experience of the sacred and the transcendent can provide health benefits, and are important coping strategies for a cancer diagnosis (20)(21) .…”
Section: Asked To Make the Prosthesis; It Was Very Similar To My Hamentioning
confidence: 99%